Assessing Corporate Sustainability in Turkish Banks: WASPAS and ARAS Approaches in the Covid-19 and the Post-Covid-19 Era - Özkan Çıtak; Ulaş Ünlü (Ekonomi, Politika & Finans Araştırmaları Dergisi, 2025)
As sustainability shifts from a voluntary commitment to a structural necessity, particularly in emerging markets, the role of the banking sector in advancing sustainable development has become increasingly vital. This study develops and applies an innovative multi-method evaluation framework to assess the sustainability performance of Turkey’s seven largest banks by asset size during the COVID-19 crisis (2020) and the subsequent recovery period (2022). Based on 75 ESG indicators aligned with international standards (GRI, UNGC, UNEP FI), data were systematically extracted from integrated reports using NVivo and analyzed through two robust MCDM techniques—WASPAS and ARAS—combined with three objective weighting methods (MEREC, CILOS, CCSD). The findings indicate that commercial banks consistently outperformed public banks, primarily due to stronger governance structures, higher levels of transparency, and greater investor pressure. A temporal comparison reveals a strategic shift: during the pandemic, banks prioritized short-term resilience measures such as employee well-being and SME support, while in the recovery phase, the focus moved toward long-term strategies including green financing, digital transformation, and innovation. Public banks remained weaker in performance throughout both periods, underscoring the need for targeted policy interventions. This study fills a significant gap in sustainability research within emerging markets and offers a practical benchmarking tool for policymakers, investors, and financial institutions navigating systemic disruptions and long-term strategic transitions.